2014
DOI: 10.14400/jdc.2014.12.10.563
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Caregiving Stress on Depression among Korean Married Adult Children of Korea

Abstract: The purpose of this study is to examine the relationship between caregivng stress and depression of the caregiver. The data was collected through by a survey on to married adults who are responsible for the care of old parents. The survey(by purposive sampling) was conducted over the course of for the three months duration from Jan. to Feb. 2014. A total of Finally, 307 copies of the questionnaire retrieved were used for analysis. First, in the case of women, those in their 50s or over, and in the all both gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Findings are mixed regarding the impact of filial obligation on adult children across cultures. For example, stronger perception or increased performance of filial obligation reportedly either increased, decreased or was not significantly associated with caregiver depression among adult children in the U.S. (Camacho et al, 2018 ; Toro et al, 2018 ), Korea (Kim et al, 2014 ), Brazil (Herrera et al, 2017 ) and China (Dong & Xu, 2016 ). Moreover, few transcultural studies or meta‐analyses have been conducted to investigate this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Findings are mixed regarding the impact of filial obligation on adult children across cultures. For example, stronger perception or increased performance of filial obligation reportedly either increased, decreased or was not significantly associated with caregiver depression among adult children in the U.S. (Camacho et al, 2018 ; Toro et al, 2018 ), Korea (Kim et al, 2014 ), Brazil (Herrera et al, 2017 ) and China (Dong & Xu, 2016 ). Moreover, few transcultural studies or meta‐analyses have been conducted to investigate this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…However, the past studies lacked comprehensive and integrated perspectives on the caregiving stress, caregiving service, depression and suicidal ideation due to the increase in the elderly population. Mainly, a study on the caregiving stress was focused on the determining factors and influencing variables [4] and some studies [5] which have shown some degree of interest on the relationship between the caregiving stress and depression. The studies only gave proposals on the problems of mental health of caregivers and that it can lead to suicides.…”
Section: Introductionmentioning
confidence: 99%